2019
DOI: 10.3126/jnps.v38i2.19028
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Using ORS and Household Management of Childhood Diarrhoea

Abstract: Introduction: Diarrhoea is defined as the passage of three or more loose stools per day. Diarrhoea is one of the leading causes of childhood mortality in India. The objectives of the study were to assess household Knowledge, Attitude and Practice for prevention of Diarrhoea in children through preformed questionnaires. Material and Methods: Four hundred and sixty eight under five children were selected for study by Cluster sampling method. Background information, details of acute diarrhoea and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…There was significant association between practice level and the knowledge and attitude levels as well as the knowledge and attitude levels, P value  .001, Table VIX [19] while other studies reported tertiary education [10,16,17] and primary education [12,20,24] as commonest. In contrast, majority of mothers in similar studies had no formal education [8,11,25,26].…”
Section: Associations Amongst Knowledge Attitude and Practice Of Part...mentioning
confidence: 83%
See 1 more Smart Citation
“…There was significant association between practice level and the knowledge and attitude levels as well as the knowledge and attitude levels, P value  .001, Table VIX [19] while other studies reported tertiary education [10,16,17] and primary education [12,20,24] as commonest. In contrast, majority of mothers in similar studies had no formal education [8,11,25,26].…”
Section: Associations Amongst Knowledge Attitude and Practice Of Part...mentioning
confidence: 83%
“…In North western Nigeria [27], more than half (59%) of the respondents associated diarrhoea with suboptimal hygienic condition and contaminated food and water whereas in Odisha, India [24] 52% had correct answers regarding the aetiology of diarrhoea. In contrast, only 24% of respondents knew the causes of diarrhoea in Al Hamza city [21], Iraq while only 17.73% had good knowledge on the causes of diarrhoea in another study in India [19]. These differences could also be due to the varying educational status of the respondents as well as varying socioeconomic status and ready access to information.…”
Section: Associations Amongst Knowledge Attitude and Practice Of Part...mentioning
confidence: 91%
“…Data were collected by using pretested, interviewer‐administered structured questionnaires. The questionnaires were developed in English after reviewing of related available literature 17,19,23,25,26 . The English version of the questionnaire was translated to regional languages of the community (Afan Oromo and Amharic).…”
Section: Methodsmentioning
confidence: 99%
“…Those mothers who able to answer above the mean of the practice assessing questions were considered as having good practice. 17 , 19 , 23 , 24 , 25 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation